Attitudes toward text recycling in academic writing across disciplines. (3rd April 2018) - Hall, Susanne; Moskovitz, Cary; Pemberton, Michael A.
ABSTRACT: Text recycling, the reuse of material from one's own previously published writing in a new text without attribution, is a common academic writing practice that is not yet well understood. While some studies of text recycling in academic writing have been published, no previous study has focused on scholars' attitudes toward text recycling. This article presents results from a survey of over 300 journal editors and editorial board members from 86 top English-language journals in 16 different academic fields regarding text recycling in scholarly articles. Responses indicate that a large majority of academic gatekeepers believe text recycling is allowable in some circumstances; however, there is a lack of clear consensus about when text recycling is or is not appropriate. Opinions varied according to the source of the recycled material, its structural location and rhetorical purpose, and conditions of authorship conditions—as well as by the level of experience as a journal editor. Our study suggests the need for further research on text recycling utilizing focus groups and interviews.